Study on Critical Failures in Power Systems: Design of IT Based Model and Implementation of SPS in Andra Pradesh State Utility - M. Balasubramanyam (New Approaches in Engineering Research Vol. 11, 2021)
Schemes to isolate failures in transmission network components are brought by power system protection. Because of the size and complexity of the power grid, it is susceptible to wide-spread cascade failures, which can result in the system collapsing in catastrophic scenarios with simultaneous outages. A form of protective scheme known as SPS/remedial action schemes (RAS) has been created to identify and prevent certain situations. This chapter goes through the simulation issues and the solution that was developed, which is unique in the real-time big power network of the AP System. The AP power system has been modelled, and a new SPS has been built, which has been successfully implemented in practise.